Marechal João Baptista Mascarenhas de Moraes : Um Herói Singelo - Machado de Oliveira Mafra, Roberto (A Defesa Nacional, 2021)
Para homenageá-lo, o autor faz um resumo da biografia do Marechal João Baptista Mascarenhas de Moraes.